Struktur Fisik dan Batin Puisi dalam Perspektif Multimodalitas pada Kanal YouTube Fiksionalisme - Widodo, Arif Wahyu; Wulandari, Sovia; Putra, Yoga Mestika; Suryani, Irma; Rahariyoso, Dwi (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
The development of digital technology has transformed conventional text-based poetry into a form of digital literature that integrates textual, auditory, and visual elements. This study aims to describe the physical and inner structures of poetry from a multimodal perspective on the Fiksionalisme YouTube channel. The research employed a qualitative descriptive method using a structuralist approach to poetry. The data consisted of words, phrases, lines, and multimodal elements, including audio and visual components, collected through observation, note-taking, and screenshot documentation techniques. The findings reveal that the physical structure of the poems is characterized by the use of connotative and metaphorical diction, dominant figurative language (metaphor, personification, hyperbole, and simile), natural free rhyme, and dynamic digital typography. The inner structure predominantly reflects themes of love, longing, admiration, and inner conflict, accompanied by romantic-melancholic tones and reflective atmospheres. From a multimodal perspective, vocal intonation, background music, and visual imagery function as integral meaning-making resources that reinforce emotional expression and audience engagement. These findings demonstrate that poetry presented on the Fiksionalisme YouTube channel represents a contemporary form of digital literature in which linguistic and multimodal elements interact synergistically to enrich literary aesthetics and appreciation in the digital era.